2021
DOI: 10.1016/j.artd.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Irrigation Solutions on the Cytotoxicity and Recovery Potential of Human Osteoblast Cells In Vitro

Abstract: Background: Surgeons use various irrigation solutions to minimize the risk of prosthetic joint infection after total joint arthroplasty. The toxicity of these solutions is an important consideration in their use. This study investigates the effect of irrigation solutions Bacitracin, Clorpactin (sodium oxychlorosene), and Irrisept (chlorhexidine) on osteoblast cytotoxicity and proliferation. Methods: Four replicates of 6 conditions at 3 time points (1, 2, and 4 min) were tested: control (normal saline), Bacitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
10
0
2
Order By: Relevance
“…Liu et al [12] also studied the effects of differing CHG dilutions on fibroblasts, myoblasts, and osteoblasts and concluded that the clinically used concentration of CHG (2%) was toxic to these cells in vitro. Same toxic effect of Irrisept on osteoblasts was shown by Markel, et al [21]. Another past study used CHG at concentrations 5–2,400 times below those used clinically on in vitro fibroblasts as well and found that the CHG totally suppressed cell proliferation [32].…”
Section: Discussionmentioning
confidence: 72%
“…Liu et al [12] also studied the effects of differing CHG dilutions on fibroblasts, myoblasts, and osteoblasts and concluded that the clinically used concentration of CHG (2%) was toxic to these cells in vitro. Same toxic effect of Irrisept on osteoblasts was shown by Markel, et al [21]. Another past study used CHG at concentrations 5–2,400 times below those used clinically on in vitro fibroblasts as well and found that the CHG totally suppressed cell proliferation [32].…”
Section: Discussionmentioning
confidence: 72%
“…We previously showed similar effects on human osteoblasts' viability and recovery after an in vitro exposure. Irrisept, Clorpactin, and Bacitracin all demonstrated some toxic effects on the cells; the damage was to some extent reversible with solutions other than Irrisept [ 21 ]. Difference in testing method (in vitro vs in vivo) should be taken into consideration when comparing studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bacitracin (33 IU/ml) and Clorpactin (sodium oxychlorosene, 0.2% dilution) were freshly prepared as aqueous solutions. The Bacitracin concentration was based on the available solution at our institution and its use in our previous in vitro study on human osteoblasts [ 21 ], while the Clorpactin concentration was based on the recommendation by original solution development [ 10 ]. Irrisept (chlorhexidine gluconate 0.05% in sterile water) and Bactisure (ethanol 1%, acetic acid 0.6%, sodium acetate 0.2%, benzalkonium chloride 0.013%, and water) were from manufactures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low viability levels registered in this last work could have been ascribed to the relatively short culture time, masking the regenerative capacity of the cells over time. Therefore, in a recent study investigating the effect of different antiseptic solutions, a longer observation time was selected as in our paper [ 46 ]. The cytotoxic effect of CHX was confirmed also at a low concentration (0.05%), with human osteoblast cells failing to recover over the course of 5 days.…”
Section: Discussionmentioning
confidence: 99%